2014
DOI: 10.1074/jbc.m114.560748
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action and Epitopes of Clostridium difficile Toxin B-neutralizing Antibody Bezlotoxumab Revealed by X-ray Crystallography

Abstract: Background: Bezlotoxumab is a neutralizing antibody targeting toxin B of Clostridium difficile. Results: The structure of bezlotoxumab bound to a fragment of toxin B reveals its epitopes and mechanism of neutralization. Conclusion: The epitopes overlap with two of the presumed carbohydrate binding pockets, preventing binding of the toxin to target host cells. Significance: The data provide a molecular basis for neutralization by this clinically important antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 44 publications
2
128
0
1
Order By: Relevance
“…1D). These data are consistent with previously observed in vitro neutralization of toxin-induced cytopathic and cytotoxic effects on mammalian cells, including gut epithelial cells, by actoxumab and bezlotoxumab (20,46,47). In addition to their protective effects against epithelial damage, the antibodies significantly decrease neutrophil recruitment to the gut wall in the ileal loop model (with a nonsignificant trend toward a decrease in the C. difficile challenge model; see Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…1D). These data are consistent with previously observed in vitro neutralization of toxin-induced cytopathic and cytotoxic effects on mammalian cells, including gut epithelial cells, by actoxumab and bezlotoxumab (20,46,47). In addition to their protective effects against epithelial damage, the antibodies significantly decrease neutrophil recruitment to the gut wall in the ileal loop model (with a nonsignificant trend toward a decrease in the C. difficile challenge model; see Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Actoxumab and bezlotoxumab bind to the receptor binding or combined repetitive oligopeptide (CROP) domains of TcdA and TcdB, respectively (20), and we have recently demonstrated that bezlotoxumab binds to regions of the CROP that overlap the putative receptor binding pockets and prevent binding of TcdB to mammalian cells (47). Despite this demonstration that bezlotoxumab directly neutralizes TcdB, the possibility exists that the antibodies may protect mice from severe inflammation at least partially through the recruitment of effector functions in host immune cells via the Fc␥ receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Actoxumab (MK-3415, GS-CDA1, and MDX-066) and bezlotoxumab (MK-6072, MBL-CDB1, and MDX-1388) are human monoclonal antibodies that target TcdA and TcdB, respectively (6). We showed previously that bezlotoxumab binds to two separate sites in the CROP domain of TcdB, partially overlapping with putative receptor binding pockets and blocking binding of the toxin to host cells (8); actoxumab, which binds to the CROP domain of TcdA (6), is presumed to work in a similar manner. In a relatively small phase II study that enrolled 200 patients in the United States and Canada, the actoxumab-bezlotoxumab combination, when given with standard-of-care therapy, reduced the rate of CDI recurrence, compared to placebo (7% and 25% recurrence, respectively) (7).…”
mentioning
confidence: 99%
“…Additionally, normal metabolismrelated fluctuations in ATP levels that are unrelated to cell viability can further affect the assay readout. We developed a more robust colorimetric assay that measures cellular protein content as a surrogate of cell growth and survival [14]. The sulforhodamine B (SRB) assay was used to determine the cytotoxic effects of purified C. difficile toxins of the reference strain VPI 10463 (ribotype 087) and from strains of ribotypes from the so-called hyper-virulent ribotypes 027 and 078.…”
Section: Toxin-induced Cytotoxicity (Step 5 Inmentioning
confidence: 99%
“…In this chapter, we describe multiple quantitative cell-based assays that were newly developed, or adapted and optimized from previous reports, and used to interrogate the effect of the C. difficile toxins on epithelial cells. The assays are validated using the highly specific and potent antitoxin antibodies, actoxumab and bezlotoxumab, which bind to and neutralize TcdA and TcdB, respectively [13][14][15].…”
Section: Introductionmentioning
confidence: 99%